Wheat Germination Is Dependent on Plant Target of Rapamycin Signaling - Smailov, Bauyrzhan; Alybayev, Sanzhar; Smekenov, Izat; Mursalimov, Aibek; Saparbaev, Murat; Sarbassov, Dos; Bissenbaev, Amangeldy (Frontiers in Cell and Developmental Biology, 2020)
Germination is a process of seed sprouting that facilitates embryo growth. The breakdown of reserved starch in the endosperm into simple sugars is essential for seed germination and subsequent seedling growth. At the early stage of germination, gibberellic acid (GA) activates transcription factor GAMYB to promote de novo synthesis of isoforms of α‐amylase in the aleurone layer and scutellar epithelium of the embryo. Here, we demonstrate that wheat germination is regulated by plant target of rapamycin signaling. TOR is a central component of the essential-nutrient–dependent pathway controlling cell growth in all eukaryotes. It is known that rapamycin, a highly specific allosteric inhibitor of TOR, is effective in yeast and animal cells but ineffective in most of higher plants likely owing to structural differences in ubiquitous rapamycin receptor FKBP12. The action of rapamycin on wheat growth has not been studied. Our data show that rapamycin inhibits germination of wheat seeds and of their isolated embryos in a dose-dependent manner. The involvement of Triticum aestivum TOR (TaTOR) in wheat germination was consistent with the suppression of wheat embryo growth by specific inhibitors of the TOR kinase: pp242 or torin1. Rapamycin or torin1 interfered with GA function in germination because of a potent inhibitory effect on α-amylase and GAMYB gene expression. The TOR inhibitors selectively targeted the GA-dependent gene expression, whereas expression of the abscisic acid-dependent ABI5 gene was not affected by either rapamycin or torin1. To determine whether the TaTOR kinase activation takes place during wheat germination, we examined phosphorylation of a ribosomal protein, T. aestivum S6 kinase 1 (TaS6K1; a substrate of TOR). The phosphorylation of serine 467 (S467) in a hydrophobic motif on TaS6K1 was induced in a process of germination triggered by GA. Moreover, the germination-induced phosphorylation of TaS6K1 on S467 was dependent on TaTOR and was inhibited by rapamycin or torin1. Besides, a gibberellin biosynthesis inhibitor (paclobutrazol; PBZ) blocked not only α-amylase gene expression but also TaS6K1 phosphorylation in wheat embryos. Thus, a hormonal action of GA turns on the synthesis of α-amylase in wheat germination via activation of the TaTOR–S6K1 signaling pathway.